Synthesis and characterization of degradable hyperbranched poly(2‐ethyl‐2‐oxazoline). Issue 19 (15th August 2019) - Ali, Muhammad Waqas; Cheng, Siyuan; Si, Jianhao; Siddiq, Muhammad; Ye, Xiaodong
ABSTRACT: Hyperbranched poly(2‐ethyl‐2‐oxazoline) was synthesized by a combination of cationic ring‐opening polymerization and the oxidation of thiol to disulfide groups. A three‐arm star poly(2‐ethyl‐2‐oxazoline) (PEtOx) was first synthesized using 1, 3, 5‐tris(bromomethyl) benzene as an initiator. The star PEtOx was end‐capped with potassium ethyl xanthate. Similarly, a linear PEtOx was synthesized and end‐capped with potassium ethyl xanthate using benzyl bromide as an initiator. Hyperbranched PEtOx was then obtained by in situ cleaving and subsequent oxidation of the star PEtOx and linear PEtOx mixture with n ‐butylamine as both a cleaving agent and a base in tetrahydrofuran. The linear PEtOx was used to prevent the formation of gel. The hyperbranched PEtOx can be cleaved with dithiothreitol to trithiol and monothiol polymer. The hyperbranched PEtOx shows no remaining thiols using Ellman's assay. The resulting hyperbranched PEtOx was hydrolyzed to a novel hyperbranched polyethyleneimine with degradable disulfide linkages. © 2019 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem. 2019, 57, 2030–2037 Abstract : Degradable hyperbranched PEtOx was obtained by in situ cleaving and subsequent oxidation of a mixture of star PEtOx and linear PEtOx with n ‐butylamine as both a cleaving agent and a base in tetrahydrofuran. The linear PEtOx was used to prevent the formation of gel.